Striving for Significance: The Relationships Between Religiousness, Spirituality, and Meaning in Life - Krok, Dariusz (Implicit religion, 2015)
The aim of this study was to investigate whether religiousness and spirituality are associated with meaning in life, and which dimensions of religiousness and spirituality show the closest links with meaning in life. It was assumed that those religious and spiritual dimensions which are most imbued with meaning would be more significant for the presence of meaning than for the search for meaning in life. Two studies were conducted. The results of Study 1 showed that the "religious meaning system" was positively associated with "meaning in life," with stronger connections for "presence of meaning" than for "search." As regards "religious coping," positive coping was positively related to presence and search, whereas negative coping was negatively associated with presence. Positive coping also had positive links with personal meaning, while negative coping had negative relations. In Study 2, overall spirituality was positively linked with search for meaning and personal meaning. Two dimensions of spirituality (harmony and ethical sensitivity) were predictors for presence of meaning, but not for search. These findings suggest that meaning in life is a crucial element of religiousness and spirituality, and is intrinsically contained within their internal structures.